Sistem Informasi Manajemen Laporan Produksi Bulanan Berbasis PHP Dan MYSQL - Aisya Qurratul A'yun (Jurnal Riset Teknik Industri, 2023)
Management information systems have an important role in a company. A good management information system will make it easier for information to be conveyed to recipients of information quickly and accurately so that it can support the activities being carried out by the company. Likewise with PT Pupuk Indonesia (Persero), especially in the production process department, by creating a monthly production report management information system, the aim is to develop an efficient and integrated management information system. This system was built using web-based technology, namely PHP as a programming language and MySQL as a database management system. This system development method involves the stages of analyzing user needs, designing database structures, developing user interfaces, implementing functionality, and testing the system. By using the waterfall method, this research ensures that each development stage is carried out carefully and meets user needs. The results of implementing this system show a significant increase in the efficiency of monthly production report management in the production process department of PT Pupuk Indonesia (Persero).